Pengaruh Pelatihan P3K Terhadap Kemampuan Evakuasi Korban Kecelakaan pada Petugas Parkir - Karyo Karyo; Suhartono Suhartono; Kusno Ferianto; Moh. Ubaidillah Faqih; Subianto Subianto (Journal of Pharmaceutical and Health Research, 2023)
Evacuation is the transfer of a person or occupant from a dangerous place to a safer place. The purpose of the study was to determine the effect of First Aid Training on the Evacuation Ability of Accident Victims in Parking Officers in Tuban District. To find out the effect of first aid training on the possibility of accident victims at parking attendants in Tuban District. Metode dalam penelitian ini adalah Pra-Eksperimental (one-group pre-post test design). Cara pengambilan sampel menggunakan simple random sampling, dengan jumlah 19 responden. Instrumen yang digunakan SOP dan lembar observasi. Analisis data menggunakan uji statistik Wilcoxon. There is an Effect of First Aid Training on Victim Evacuation Ability Accident to Parking Officers in Tuban District.